PENGGUNAAN EJAAN VAN OPHUIJSEN PADA NAMA JALAN DI SURABAYA: KAJIAN LINGUISTIK DIAKRONIS - Alya Rizky Ika Putri; Endang Sholihatin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines changes in the spelling of street names in the city of Surabaya from the past to the present. Street names not only serve as locational markers but also reflect historical, social, and linguistik developments within the community. The purpose of this study is to identify the patterns of spelling changes in street names in Surabaya and to analyze these changes through a diachronic linguistik approach. The research employed a descriptive qualitative method, utilizing the book *Soerabaia Tempoe Doeloe: Buku 2* by Dukut Imam Widodo as its primary data source, specifically the sections discussing street names in Surabaya during the colonial era. The data collected comprised 15 street names written using the Van Ophuijsen spelling system. The results indicate that the most prevalent spelling changes were the substitution of “oe” with “u,” “tj” with “c,” “dj” with “j,” and “nj” with “ny.” These changes reflect a process of simplification and adaptation from the old spelling system to modern Indonesian spelling, while preserving the historical identity and value of the street names.